How the Marketing and Selling of Books by Authors of Colour Produces Racial Inequalities in Publishing - Saha, Anamik; van Lente, Sandra (Mémoires du livre / Studies in Book Culture, 2022)
Based upon a unique empirical study on diversity in UK publishing involving over 110 interviews with publishers, this paper explores the obstacles facing authors of colour. While the underrepresentation of authors from minoritized backgrounds is generally seen as a problem of acquisition, we identify what political economist Nicholas Garnham calls the “cultural distribution” stage as the most critical for authors of colour. Specifically, we demonstrate how racialized assumptions about audiences as articulated and mobilized by people working in promotion, sales, and retail impede the progress of these authors. We argue that racial inequalities in publishing are a product of how racially and ethnically minoritized audiences are undervalued, culturally as well as economically. Adopting a postcolonial cultural economy approach, we identify the areas where antiracist activism needs to be focused in order to address racial inequalities in publishing in a more impactful way.